Computer-Vision in Industrial Automation and Mobile Robots - Grilo, Frederico (2019)
Computer vision is presently a very relevant and important tool in both industrial manufacturing and mobile robots. As human vision is the most relevant sense to feed the brain with environmental information for decision making, computer-vision is nowadays becoming the main artificial sensor in the domains of industrial quality assurance and trajectory control of mobile robots.